What is the evidence of effectiveness of non-pharmaceutical, non-surgical, biopsychosocial interventions for body image and pain management in individuals with endometriosis? A systematic review. Issue 4 (December 2022) - Falconer, Laura; Hendricks, Emma; Harcourt, Diana
Aim: To identify and review the success of non-pharmaceutical, non-surgical biopsychosocial interventions in individuals with endometriosis, in managing pain and improving body image. Methods: Cochrane, EBSCO, IBSS, NICE, Open Grey, OVID, Proquest, Scopus and Science Direct were searched in April 2021, using inclusion and exclusion criteria. Data collection and analysis: Five randomised control trials, and one controlled clinical trial resulted from the search. Study quality was assessed using the Effective Public Health Practice Project (EPHPP) Quality Assessment Tool. Studies were synthesised by intervention type, into physical only, and physical and psychological. Results: Across the six papers, 323 participants were recruited, through medical records or self-referral, and treatments largely administered by specialist practitioners. From the EPHPP quality assessment, 2 weak quality papers, and four moderate quality papers found improvements to pain, with large effect sizes in four papers. No studies used established body image measures to examine intervention effects on body image, and all lacked health psychology theoretical basis. There were common issues in selection bias, confounders and blinding. Conclusion: Without gold-standard methodology, evidence of effectiveness cannot be concluded. However, there is promising rationale if these issues are addressed.